Arabic Imperfect Verbs in Translation: A Corpus Study of English Renderings - Gadalla, Hassan (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThis paper proposes a model for translating Standard Arabic imperfect verbs into English based on their contextual references. It starts with a brief introduction to tense and aspect in English and Arabic. Then, it shows the study aim and technique. After that, it provides an analysis of the study results by discussing the various translations of Arabic imperfect verbs in the translations of two novels written by Naguib Mahfouz. The study compares the translations with the original texts to highlight the different English renderings of the Arabic imperfect verbs.